Acute alcohol consumption elevates serum bilirubin: An endogenous antioxidant. (1st April 2015) - O'Malley, Stephanie S.; Gueorguieva, Ralitza; Wu, Ran; Jatlow, Peter I.
Highlights: Serum bilirubin was measured before and after acute alcohol consumption. Bilirubin, an endogenous antioxidant, increased in nonsmokers but not in smokers. Bilirubin concentrations correlate with favorable health outcomes. Effects on bilirubin may explain some of the positive effects of alcohol on health. Abstract: Background: Moderate alcohol consumption has been associated with both negative and favorable effects on health. The mechanisms responsible for reported favorable effects remain unclear. Higher (not necessarily elevated) concentrations of serum bilirubin, an antioxidant, have also been associated with reduced risk of cardiovascular disease and all-cause mortality. This study tests the hypothesis that single dose alcohol consumption elevates bilirubin providing a potential link between these observations. Methods: 18 healthy individuals (eight cigarette smokers) were administered alcohol, calibrated to achieve blood concentrations of 20, 80 and 120 mg/dL, in random order in three laboratory sessions separated by a week. Each session was preceded by and followed by 5–7 days of alcohol abstinence. Serum bilirubin was measured at 7:45 a.m. prior to drinking, at 2 p.m., and at 7:45 the next morning. Mixed effects regression models compared baseline and 24 h post-drinking bilirubin concentrations. Results: Total serum bilirubin (sum of indirect and direct) concentration increased significantly after drinking from baseline to 24 h in non-smokers (from M = 0.38, SD = 0.24 to M = 0.51, SD = 0.30, F (1, 32.2) = 24.24, p < .0001) but not in smokers (from M = 0.25, SD = 0.12 to M = 0.26, SD = 0.15, F (1, 31.1) = 0.04, p = 0.84). In nonsmokers the indirect bilirubin concentration and the ratio of indirect (unconjugated) to direct (conjugated) bilirubin also increased significantly. Conclusions: Alcohol consumption leads to increases in serum bilirubin in nonsmokers. Considering the antioxidant properties of bilirubin, our findings suggest one possible mechanism for the reported association between alcohol consumption and reduced risk of some disorders that could be tested in future longitudinal studies.